Hybrid Maize in Bukavu - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
Thanks to AID-I GLR interventions in South Kivu, DRC, two local seed companies; AGRI-FORCE and ETS Munga; have started producing hybrid maize. For this, they are supported by Seed System Group (SSG), a scaling partner